PERAN BIDAN DESA DALAM PENGEMBANGAN KESEHATAN MASYARAKAT MELALUI PENGELOLAAN DESA SIAGA DI KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN PROVINSI SULAWESI UTARA - , Femmy K. Keintjem, Dra. Yayi Suryo Prabandari, M.Si, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Development of health in Indonesia from 2010 to 2014 is aimed to increase access to basic, low-price and achievable health with main priorities such as increasing health of mothers, babies, underfive- year children, and panned family, which will be achieved by a societal empowerment strategy. In performance of alert village, village midwives are health workers widely playing their roles in developing societal health according to their roles, namely as educators, motivators, facilitators, and mediators in moving and empowering society to achieve autonomy and effort to increase health, especially health care service to mothers and children. Objective: To get description about the roles of village midwives in developing societal health through management of alert village in subdistrict of Amurang Timur. Methods: This research was qualitative research using case study design. Subjects consisted of primary informants, village midwives